2011
DOI: 10.1186/1476-511x-10-163
|View full text |Cite
|
Sign up to set email alerts
|

Renal tissue alterations were size-dependent with smaller ones induced more effects and related with time exposure of gold nanoparticles

Abstract: BackgroundGold nanoparticles (GNPs) have important application for cell labeling and imaging, drug delivery, diagnostic and therapeutic purposes mainly in cancer. Nanoparticles (NPs) are being increasingly exploited for medical applications. The aim of the present study was to investigate the particle-size and period effects of administration of GNPs on the renal tissue in an attempt to address their potential toxicity.MethodsA total of 70 healthy male Wistar-Kyoto rats were exposed to GNPs received 50 or 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 22 publications
0
55
0
Order By: Relevance
“…Apoptotic alteration might be followed by organelles swelling, specially mitochondria, endoplasmic reticulum, and rupture of lysosomes which might lead to amorphous eosinophilic cytoplasm as an initial sign in the sequence of hepatocytes necrosis before shrinking and dissolution of nuclei [13, 14]. The seen hepatocytes necrosis due to GNPs exposure might indicate oxidative stress on these cells by glutathione depletion [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic alteration might be followed by organelles swelling, specially mitochondria, endoplasmic reticulum, and rupture of lysosomes which might lead to amorphous eosinophilic cytoplasm as an initial sign in the sequence of hepatocytes necrosis before shrinking and dissolution of nuclei [13, 14]. The seen hepatocytes necrosis due to GNPs exposure might indicate oxidative stress on these cells by glutathione depletion [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…Propolis subjection improved glomerular, intertubular, and interstitial capillary dilatation induced by GNPs. This might indicate potential capability of propolis to suppress glomerular filtration surface and interstitial renal capillary expansion related to its ability to prevent lipid peroxidation by activation of some antioxidant enzymes 14,17,29 . Several studies reported that propolis could protect the mitochondria and cellular macromolecules against oxidative damage [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…GNPs demonstrated oxidative stress and macromolecules interaction that could result in histocytotoxicity [9][10][11] . Some research works showed that GNPs with a size of of 5-20 nm were more toxic and had long time accumulation than the larger ones in the vital organs including the kidney [12][13][14] . The kidneys receive high blood flow and have high exposure to small GNPs with long circulating residue than the larger ones 9,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Abdelhalim and Jarrar clearly observed damage to proximal tubular epithelial cells in rats exposed to GNPs. 34,35 Furthermore, numerous metallic nanoparticles are selective nephrotoxicants that preferentially accumulate in the kidneys, further to induce renal injury. [36][37][38][39] It has been known for some time that chronic kidney diseases (CKD) are often accompanied by hypoxic, which may play an important pathogenic role in the development of renal damage; 40 whereas, no study has been performed concerning GNP interactions with hypoxic kidney cells, especially proximal tubules.…”
Section: Introductionmentioning
confidence: 99%